Concept, Nature, Significance and Techniques in Business Environment Management - Amal Joseph (AG Volumes, 2021)
A business organisation has to transact and interact with the environment in which it operates. The factors included in business and the environment is interrelated and mutually interdependent. The business environment includes all of the factors that affect or influence the business’s operations and determine its effectiveness. Understanding the environment within which the business operates is very important to understanding and analysing the running of a business unit. Environmental factors influence every aspect of the business, including location, production, price determination, management, transportation, and distribution. The chapter discusses the nature, concepts, significance, and techniques used in business environment management.